Drosophila comet assay: insights, uses, and future perspectives - Gaivão, Isabel; Sierra, L. María (Frontiers in Genetics, 2014)
The comet assay, a very useful tool in genotoxicity and DNA repair testing, is being applied to Drosophila melanogaster since around 15 years ago, by several research groups. This organism is a valuable model for all kind of processes related to human health, including DNA damage response. The assay has been performed mainly in vivo using different larvae cell types (from brain, midgut, hemolymph and imaginal disc), but also in vitro with the S2 cell line. Since its first application, it has been used to analyze the genotoxicity and action mechanisms of different chemicals, demonstrating good sensitivity and proving its usefulness. Moreover, it is the only assay that can be used to analyze DNA repair in somatic cells in vivo, comparing the effects of chemicals in different repair strains, and to quantitate repair activities in vitro. Additionally, the comet assay in Drosophila, in vivo and in vitro, has been applied to study the influence of protein overexpression on genome integrity and degradation. Although the assay is well established, it could benefit from some research to determine optimal experimental design to standardize it, and then to allow comparisons among laboratories independently of the chosen cell type.